(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Socioeconomic Characteristics and Income of Clove Traders in Banyuatis Village, Banjar District, Buleleng Regency. Banyuatis Village is one of the clove-producing villagesin Buleleng Regency. The characteristics of each clove trader in Banyuatis Village are different in carrying out the clove marketing system, so it is very important to know considering that clove traders play an important role in the clove marketing system. Fluctuations in clove yield occur due to climatic influences, besides that sometimes cause an oversupply of cloves which causes very sharp price fluctuations. This study aims to determine the socioeconomic conditions of clove traders in Banyuatis Village. The research methods used in this study are qualitative descriptive analysis and quantitative analysis. The results showed that the total income of clove traders in Banyuatis Village was Rp. 631.878.653/3 months with an average per month of Rp. 210.626.217,6. 7 tons – 20 tons with 22 respondents or 16 respondents majeg and six respondents not majeg. Respondents with a sales volume of 21 tons – 34 tons were six majeg respondents and one non-majeg respondent. There is only one majeg respondent with a sales volume of 35 tons – 50 tons. Respondents in this study, the sample consisted of 30 clove traders from Banyuatis Village, Banjar District, Buleleng Regency. Characteristics observed in this sample include age, gender, recent education, business experience and number of dependents. While the social impact is the existence of majeg culture which is a method of buying cloves directly from the tree which is characteristic of clove traders, as well as cooperation between traders that makes it easier to find capital and markets.